The determinant of brand awareness: Lesson from Indonesia - Levita Dianty; Rizal Hari Magnadi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
This study analyzes the effect of advertising creativity, jingles and endorsers on brand awareness using Multiple Linear Regression Analysis on 150 respondents in Semarang. The results showed that advertising creativity, jingles and endorsers have a positive and significant influence on brand awareness. Advertising creativity is the strongest variable affecting brand awareness. Companies need to use this variable as the most important factor because it has positive impacts.